To what extent do Latin Americans trust and cooperate? Field experiments on social exclusion in six Latin American countries - Juan Camilo Cárdenas; Alberto Chong; Hugo \~Nopo (Inter-American Development Bank, Research Department, 2008)
This paper explores the extent to which individuals trust, reciprocate, cooperate and pool risk by using a battery of field experiments containing the trust game, the voluntary contributions mechanism and the risk pooling game; applied in six capital cities in Latin America. The results suggest that: (i) on average, the propensity to trust and cooperate among Latin Americans is remarkably similar to that found in other regions of the world; (ii) expectations about the behavior of other players are the main driver of trust, reciprocity and cooperation; and (iii) behaviors involving socialization, trust and cooperation are closely interconnected.
Keywords: 330; Soziale Gruppe; Soziale Isolation; Soziales Verhalten; Verhaltensökonomik; Test; Lateinamerika